Les prélèvements et les analyses sur l’os humain ancien : connaître, encadrer et promouvoir la recherche. Retour sur le rapport rendu dans le cadre du groupe de travail sur la mise en place des protocoles de prélèvements et d’analyses sur l’os humain ainsi que sur la conservation des échantillons (PAOHCE) - Christian Cribellier; Anne Chaillou (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
In 2019, the French Ministry of Culture’s department for archaeology set up a working group on the implementation of protocols for sampling and analysing human bones and the preservation of bone samples. The working group produced a report in 2022 on its contributions to the definition of good practices for sampling and analysing human bone under the best possible conditions and to ways of setting up administrative procedures that ensure better management of requests for sample analysis and their follow-up. This article reviews the genesis of the working group and the discussions and recommendations presented in its report. The recommendations concern the need for continuing efforts to raise awareness in the scientific community (via fact sheets) about the preservation of anthropological remains and their potential value for research, for implementation of a procedure for supervising and assessing research projects and, finally, for reporting on the work and the procedures implemented.